Celebrating Adam Watkins' Fifth Birthday at Home - Watkins, Howard::::::::: (1983)
?, Diane Gomez, Doreen Gomez, Linda Gomez, David Gomez, Rose Watkins, Adam Watkins, Albert Watkins, Christine Watkins holding Robin Watkins, Howard Watkins Citron tree full of fruit in background